Studi Komparasi Preferensi Konsumen atas Harian Umum Suara Merdeka dan Tribun Jateng di Kota Semarang - Angga Maulana; Bulan Prabawani; Sendhang Nurseto (Jurnal Ilmu Administrasi Bisnis, 2015)
The aim of this research is to know the differences of consumer preferences between Suara Merdeka daily newspaper and Tribun Jateng. The population taken in this research are consumers who ever bought Suara Merdeka daily newspaper and Tribun Jateng. Samples used in this research some 100 respondents used by non-probability sampling technique with approach accidental sampling ( the sample based on chance ). A method of analysis used is quantitative analysis that is using different Independent Sample T- test. The benefit factor is a factor that most distinguishes between Suara Merdeka daily newspaper with Tribun Jateng, with t-test 8,872 then followed by reader responsiveness of 5,005, marketing of 0,334, and quality of content and physical of -0,145. Hypothesis testing is done using different test showed that consumers preferences of the difference occurred against the benefit factor and reader responsiveness. All indicators of the benefits and reader responsiveness Suara Merdeka is superior than Tribun Jateng. But consumer preferences of differences did not happen to the quality of content and physical factor and marketing factor. Based on data obtained that Tribun Jateng can match the quality of content and physical factor and marketing factor of Suara Merdeka. While perception most dominant based on response respondents is the existence of newspapers for Suara Merdeka and actuality of news for Tribun Jateng.